An STM Perspective on Hexaborides: Surface States of the Kondo Insulator SmB6. Issue 12 (17th October 2021) - Wirth, Steffen; Schlottmann, Pedro
Abstract: Compounds within the hexaboride class of materials exhibit a wide variety of interesting physical phenomena, including polaron formation and quadrupolar order. In particular, SmB6 has recently drawn attention as it is considered a prototypical topological Kondo insulator. Evidence in favor of this concept, however, has proven experimentally difficult and controversial, partly because of the required temperatures and energy resolution. Here, a powerful tool is scanning tunneling microscopy (STM) with its unique ability to give local, microscopic information that directly relates to the one‐particle Green's function. Yet, STM on hexaborides is met with its own set of challenges. This article attempts to review the progress in STM investigations on hexaborides, with emphasis on SmB6 and its intriguing properties. Abstract : Hexaborides are a versatile family of compounds. Recently, SmB6 gained tremendous research interest because of its proposed topologically non‐trivial surface properties. This article not only reviews results on SmB6 obtained by scanning tunneling microscopy, a particularly surface sensitive technique which can also be used for spectroscopic measurements, but also puts them into perspective to findings on other hexaborides.